Potential work-life balance risks to HR management in the military: bibliometric analysis - Milan Jan Půček; Renata Skýpalová; Veronika Linhartová (Cogent Business & Management)
The ongoing war in Ukraine has drawn attention both to combat operations and military personnel readiness for action. Unlike classified security information, human resource management and risks associated with work-life balance and prioritization of family over army service remain an open research subject. This paper aims to examine publication feedback on current HRM trends in the perception of work-life balance, recognizing the potential risk of prioritizing personal life over military service. The data set consists of almost four hundred scientific studies published from 2000 to 2023 and indexed in the Web of Science. Using the VOSviewer software, a bibliometric analysis was performed, focusing on co-authorship, citation cartography and reference linking. The findings indicate a growing research interest in the issue, most of the relevant journal articles being published in the United States. Keyword cluster analysis suggests that the most frequent research topics are military deployments and performance, while, e.g., HR and career development or life and job satisfaction receive less attention.